Grain boundary and surface doped rare earth zirconium based ceramic material, its manufacturing method and use

JP2025505108AActive Publication Date: 2025-02-21GUOKE RE ADVANCED MATERIALS CO LTD +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024542108
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2023-02-13
Publication Date
2025-02-21
Estimated Expiration
2043-02-13

Smart Images

  • Figure 2025505108000001_ABST
    Figure 2025505108000001_ABST
Patent Text Reader

Abstract

The present invention relates to a rare earth zirconium-based ceramic material doped on grain boundaries and surfaces, its preparation method and application, and by using a stepwise doping method, some doping elements are located on the grain boundaries and surfaces of the rare earth zirconium-based ceramic material, and the sintering activity of the rare earth zirconium-based ceramic material can be changed by adjusting the type and content of the doping elements on the grain boundaries and surfaces, thereby adjusting the grain size, grain boundary number and properties of the rare earth zirconium-based ceramic material, and finally optimizing the electrical, mechanical and other properties of the material. The doping method used has the advantages of simple process, low cost and high versatility, can meet the demand for doping elements of different rare earth zirconium-based ceramics, and is suitable for large-scale application. The rare earth zirconium-based ceramic material obtained by adopting the technical solution of the present invention can be used in different fields such as polishing media, optical fiber connectors, mobile phone backplates, dental materials, bioceramics, thermal barrier coatings, oxygen sensors or nitrogen-oxygen sensors, and solid oxide fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] <CROSS REFERENCE TO RELATED APPLICATIONS> This application is filed based on a Chinese patent application bearing application number 202210135456.3 and filing date February 14, 2022, and claims priority to the Chinese patent application, the entirety of which is incorporated herein by reference.

[0002] The present invention relates to the technical field of ceramic materials, in particular to grain boundary and surface doped rare earth zirconium based ceramic materials, their preparation methods and applications. [Background technology]

[0003] Rare earth zirconium-based ceramic materials have excellent physical and chemical properties, and are currently widely used in high-end fields such as defense and military industry, biomedicine, new energy, electronic information, and automobiles. For example, in the biomedical field, its good biocompatibility and mechanical performance make it the most ideal dental restoration material at present. In the information and communications field, its high strength, high toughness and no-signal shielding properties make it the preferred housing material for 5G mobile phones. In the aviation field, its excellent thermal insulation and high temperature stability make it a very important material for the thermal barrier coating of aircraft engines. In environmental protection, its corrosion resistance and oxygen ion conductivity make it an important material for vehicle oxygen sensors or nitrogen oxygen sensors. In the energy field, its high oxygen ion conductivity makes it the most promising electrolyte material for solid oxide fuel cells.

[0004] As described above, improving the mechanical and electrical properties of rare earth zirconium-based ceramic materials is the key to improving their performance. Doping modification is a common method for improving the performance of rare earth zirconium-based ceramics. Previous research has shown that doping with Ce can significantly improve the toughness of rare earth zirconium-based ceramics, and such materials have already been applied in special structural components and grinding media in special industries. Doping elements such as Ni, Er, and Yb can significantly reduce the thermal diffusion coefficient and thermal conductivity of rare earth zirconium-based ceramics, making them potential new thermal barrier coating materials. Doping with Yb, Gd, or Ce can improve the ionic conductivity of rare earth zirconium-based ceramics, which helps prevent high-temperature phase transition and improves the thermal stability of the material. Doping such rare earth zirconium-based ceramics has attracted widespread attention in the fields of gas sensors, solid oxide fuel cells, and the like. However, there is an obvious limit to improving the performance of rare earth zirconium-based ceramics by simple element doping, and the requirements for the performance of rare earth zirconium-based ceramic materials in modern application fields are becoming increasingly higher, so that the mechanical, electrical and other properties of rare earth zirconium-based ceramic materials need to be further improved. Summary of the Invention [Problem to be solved by the invention]

[0005] Based on the above situation in the prior art, the present invention aims to provide a rare earth zirconium-based ceramic material doped with grain boundaries and surfaces, which can be modified in sintering activity according to different kinds and contents of doping elements by doping specific elements in the grain boundaries and surfaces of rare earth zirconium-based ceramic powder materials, thereby adjusting the crystal grain size, grain boundary number and grain boundary characteristics, improving the physicochemical performances such as material strength, thermal shock resistance, ionic conductivity, etc., and meeting the requirements of different application fields such as bioceramics, thermal barrier coatings, oxygen sensors or nitrogen oxygen sensors, solid oxide fuel cells, etc., as well as a manufacturing method and application thereof. [Means for solving the problem]

[0006] In order to achieve the above object, a first aspect of the present invention provides a rare earth zirconium-based ceramic material doped at grain boundaries and surfaces, the rare earth zirconium-based ceramic material having a chemical formula of RE x Zr 1-x-y M y O 2-z where: RE is a rare earth element, M is the doping element of the cation, 0.03≦x≦0.5, 0 <y≦0.15、0.01≦z<0.3である。

[0007] Furthermore, the RE is one or a combination of one or more of Sc, Y, La, Gd, and Ce.

[0008] Furthermore, M includes one or a combination of one or more of cationic transition metal elements, alkaline earth metal elements, Al, Ga, In, Ge, Sn, Sb, Bi, Si, and rare earth elements.

[0009] Furthermore, the M is one or a combination of one or more of Mg, Ca, Sr, Al, Ga, V, Fe, Mn, Ni, Zn, Nb, In, Bi, and rare earth elements, preferably one or a combination of one or more of Mg, Sr, Al, V, Ni, Bi, La, Ce, Pr, Nd, Sm, Eu, Gd, Er, Yb, Lu, Y, and Sc, and more preferably one or a combination of one or more of Mg, Al, Ni, Bi, La, Ce, Gd, Yb, and Lu.

[0010] Furthermore, the molar content of M in the rare earth zirconium based ceramic material is 15% or less, and preferably 10% or less.

[0011] Furthermore, the rare earth zirconium-based ceramic material contains an oxide of M at the grain boundaries and on the surface.

[0012] Furthermore, the rare earth zirconium based ceramic material has one or more of a cubic fluorite structure, a tetragonal phase, a monoclinic phase and a rhombohedral phase, and preferably has one or two of a cubic fluorite structure and a tetragonal phase.

[0013] In a second aspect of the present invention, there is provided a method for producing a grain boundary and surface doped rare earth zirconium based ceramic material according to the first aspect of the present invention, comprising the steps of: Step S1: mixing aqueous solutions of RE and Zr compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; filtering, washing, drying and roasting the obtained precipitate to obtain a rare earth zirconium oxide powder; and step S2, mixing the rare earth zirconium-based oxide powder material obtained in step S1 with a liquid salt of a doping element M, drying, heat treating it once or twice, and then firing it once or twice to obtain a rare earth zirconium-based ceramic material doped at the grain boundaries and on the surface.

[0014] In a third aspect of the present invention there is provided a method for producing the grain boundary and surface doped rare earth zirconium based ceramic material according to the first aspect of the present invention, comprising: Step S1: mixing aqueous solutions of RE, Zr and some M compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; filtering, washing, drying and roasting the obtained precipitate to obtain a rare earth zirconium-based oxide powder containing the M element; and step S2, mixing the rare earth zirconium-based oxide powder containing the M element obtained in step S1 with the liquid salt of the remaining doping element M, drying, heat treating once or twice, and firing once or twice to obtain a rare earth zirconium-based ceramic material doped on the grain boundaries and surfaces.

[0015] Furthermore, the aqueous solution containing Zr in step S1 includes one or a combination of one or more aqueous solutions of zirconium oxychloride, zirconium oxynitrate, zirconium oxysulfate, zirconium acetate, and zirconium citrate.

[0016] Further, the RE-containing aqueous solution in step S1 includes one or a combination of one or more aqueous solutions of rare earth chlorides, nitrates, sulfates, acetates, and citrates.

[0017] Furthermore, the liquid salts of the doping elements M include one or a combination of more than one of the following molten salts or aqueous solutions: chlorides, nitrates, sulfates, acetates, citrates and amino acid salts.

[0018] Furthermore, the basic substance includes at least one of magnesium hydrogen carbonate, urea, and hydroxide, carbonate, or hydrogen carbonate of at least one element of ammonium, sodium, and potassium, and is preferably at least one of sodium hydroxide, urea, ammonia water, and ammonium hydrogen carbonate.

[0019] Furthermore, the pH value during the precipitation process in step S1 is controlled to 4.5 to 14, and preferably 5 to 11, the pH value at the end of the precipitation is controlled to 8 to 13, and preferably 9 to 11, and the temperature during the precipitation is 0 to 120°C, and preferably 10 to 80°C.

[0020] Furthermore, the roasting temperature described in step S1 is 600 to 1100° C., preferably 650 to 950° C., and the roasting time is 1 to 24 hours, preferably 3 to 15 hours.

[0021] Furthermore, the heat treatment temperature in step S2 is 200 to 750° C., preferably 400 to 600° C., and more preferably 400 to 550° C., and the heat treatment time is 1 to 24 hours, and preferably 1 to 12 hours.

[0022] Furthermore, the firing temperature described in step S2 is 700 to 1200° C., preferably 800 to 1100° C., and more preferably 900 to 1100° C., and the firing time is 1 to 24 hours, and preferably 3 to 15 hours.

[0023] In a fourth aspect of the present invention, there is provided the use of the grain boundary and surface doped rare earth zirconium based ceramic powder material according to the first aspect of the present invention in the fields of polishing media, fiber optic connectors, mobile phone backplates, dental materials, bioceramics, thermal barrier coatings, oxygen or nitrogen oxygen sensors, and solid oxide fuel cells. Effect of the Invention

[0024] As described above, the present invention provides a rare earth zirconium-based ceramic material doped with grain boundaries and surfaces, and its manufacturing method and use, and the doping element is located on the grain boundaries and surfaces of the rare earth zirconium-based ceramic material by the grain boundary doping method. According to the difference in the valence, atomic radius, content, etc. of different doping elements, the doping of grain boundaries and surfaces can change the sintering activity of the rare earth zirconium-based ceramic material, thereby adjusting the grain size, grain boundary number and grain boundary characteristics. When the doping element improves the sintering activity and reduces the grain boundary number, it reduces the grain boundary resistance of the rare earth zirconium-based ceramic material, thereby improving the ionic conductivity of the rare earth zirconium-based ceramic material; when the doping element reduces the sintering activity and increases the grain boundary number, it causes the grain refinement of the rare earth zirconium-based ceramic material, thereby improving the mechanical performance and high temperature stability of the rare earth zirconium-based ceramic material. The grain boundary and surface doping method provided in the technical solution of the present invention is versatile, and can realize the efficient and low-cost improvement of the mechanical, electrical and thermal performance of rare earth zirconium-based ceramic materials, and can meet the demands of doping elements for different rare earth zirconium-based ceramic materials. [Brief description of the drawings]

[0025] [Figure 1]1 is a flow chart of a method for making the grain boundary doped rare earth zirconium based ceramic of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below with reference to the drawings in conjunction with specific embodiments. It should be understood that these descriptions are illustrative and do not limit the scope of the present invention. In addition, in the following description, descriptions of well-known structures and techniques are omitted to avoid unnecessary confusion of the concept of the present invention.

[0027] A first aspect of the present invention provides a grain boundary and surface doped rare earth zirconium based ceramic material, the chemical formula of which is RE x Zr 1-x-y M y O 2-z where RE is a rare earth element, M is a cationic doping element, and 0.03≦x≦0.5, 0 <y≦0.15、0.01≦z<0.3である。

[0028] Here, RE may be one or a combination of Sc, Y, La, Gd and Ce, and the cationic doping element M may be one or a combination of cation transition metal elements, alkaline earth metal elements, Al, Ga, In, Ge, Sn, Sb, Bi, Si and rare earth elements, preferably M is one or a combination of cation transition metal elements, alkaline earth metal elements, Al, Ga, In, Ge, Sn, Sb, Bi, Si and rare earth elements, more ... The molar content of the cationic doping element M in the rare earth zirconium based ceramic material is less than 15%, preferably less than 10%. The cationic doping element M is located at the grain boundaries and surfaces of the rare earth zirconium based ceramic material, or located at the grain boundaries, surfaces and grains. The cationic doping element M is transformed into one or more of oxides, nitrogen-containing compounds and their composites at the grain boundaries and surfaces of the rare earth zirconium based ceramic material, or located at the grain boundaries, surfaces and grains. The rare earth zirconium based ceramic material may be one or more of the following: cubic fluorite structure, tetragonal phase, monoclinic phase and rhombohedral phase, preferably one or two of the following: cubic fluorite structure and tetragonal phase.

[0029] The rare earth zirconium-based ceramic material provided in the embodiments of the present invention can obtain different rare earth zirconium-based ceramic powders by changing the doping element and adjusting the doping process, and can be applied to different scenes. The grain boundary and surface of the rare earth zirconium-based ceramic material can contain oxides of M by doping the grain boundary and surface with cationic element M, and the grain boundary characteristics of the rare earth zirconium-based ceramic material can be changed according to the different types and contents of doping elements, thereby adjusting the crystal grain size, grain boundary number and properties of the rare earth zirconium-based ceramic material, and finally optimizing the electrical, mechanical, thermal and other properties of the material. Doping the grain boundary and surface with a certain type of cationic element M can improve the sintering activity and reduce the grain boundary, which is favorable to the transition of oxygen ions at the grain boundary, and reduces the grain boundary resistance of the rare earth zirconium-based ceramic material, thereby effectively improving its ionic conductivity. Doping the grain boundaries and surface with other cationic elements M can reduce the sintering activity of the rare earth zirconium-based ceramic material, refine the crystal grains, pin the grain boundaries, and improve the mechanical properties such as fracture toughness and bending strength and high temperature stability of the rare earth zirconium-based ceramic material. In addition, considering that doping with more than 15 mol% of cationic doping element M will increase the degree of lattice distortion, which will affect the ionic conductivity and mechanical properties of the material, the molar content of cationic doping element M in the rare earth zirconium-based ceramic material in the present invention is also limited.

[0030] In a second aspect of the present invention, there is provided a method for producing the grain boundary and surface doped rare earth zirconium based ceramic material according to the first aspect of the present invention, the flow chart of which is shown in FIG. 1 , Step S1: mixing aqueous solutions of RE and Zr compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; filtering, washing, drying and roasting the obtained precipitate to obtain a rare earth zirconium oxide powder; and step S2, mixing the rare earth zirconium-based oxide powder obtained in step S1 with a liquid salt of a doping element M, drying, heat treating once or twice, and then firing once or twice to obtain a rare earth zirconium-based ceramic powder doped at the grain boundaries and on the surface.

[0031] In a third aspect of the present invention there is provided a method for producing the grain boundary and surface doped rare earth zirconium based ceramic material according to the first aspect of the present invention, comprising: Step S1: mixing aqueous solutions of RE, Zr and some M compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; filtering, washing, drying and roasting the obtained precipitate to obtain a rare earth zirconium-based oxide powder containing the M element; and step S2, mixing the rare earth zirconium-based oxide powder containing the M element obtained in step S1 with the liquid salt of the remaining doping element M, drying, heat treating once or twice, and firing once or twice to obtain a rare earth zirconium-based ceramic material doped on the grain boundaries and surfaces.

[0032] In the technical solutions of the above two manufacturing methods, the solution containing Zr in step S1 includes one or a combination of one or more aqueous solutions of zirconium oxychloride, zirconium oxynitrate, zirconium oxysulfate, zirconium acetate and zirconium citrate, and the solution containing RE in step S1 includes one or a combination of one or more aqueous solutions of rare earth chloride, nitrate, sulfate, acetate and citrate. The basic substance includes at least one of magnesium hydrogen carbonate, urea and hydroxide, carbonate or hydrogen carbonate of at least one element of ammonium, sodium and potassium, preferably at least one of sodium hydroxide, urea, ammonia water and ammonium hydrogen carbonate. The pH value of the precipitation process in step S1 is controlled to 4.5-14, preferably 5-11, the pH value at the end of precipitation is controlled to 8-13, preferably 9-11, and the temperature during precipitation is 0-120°C, preferably 10-80°C. The liquid salt of the doping element M includes one or a combination of one or more of nitrates, acetates, citrates, and amino acid salts, which are molten salts or aqueous solutions. Here, the molar ratio of M at the grain boundaries and surface is 10-70%. The morphology and ratio of M at the grain boundaries and surface can be adjusted by controlling the precipitation conditions, the heat treatment of the product, and the firing temperature, time, atmosphere, etc.

[0033] In step S1, the roasting temperature is 600 to 1100° C., preferably 650 to 950° C., and the roasting time is 1 to 24 hours, preferably 3 to 15 hours.

[0034] In step S2, the heat treatment temperature is 200-750°C, preferably 400-600°C, more preferably 400-550°C, the heat treatment time is 1-24h, preferably 1-12h, the sintering temperature is 700-1200°C, preferably 800-1100°C, more preferably 900-1100°C, the rare earth zirconium ceramic powder obtained above can be effectively controlled in strength and dispersibility by sintering once or twice, and after sintering once, ball milling and surface treatment can be used to avoid two sintering aggregations. Within this temperature range, the doping element can preferentially enter the grain boundary, and below this temperature range, the doping element is difficult to enter the grain boundary, and above this temperature range, the doping element enters the solid phase, sintering becomes excessive, and the grain boundary is reduced, and the sintering time is 1-24h, preferably 3-15h. The morphology and proportion of M in the grain boundaries and on the surface are adjusted and controlled by controlling the precipitation parameters, the heat treatment of the product, and the firing temperature, time, atmosphere, etc. In order to meet the special requirements for the ceramic performance of different applications, it is necessary to adjust or change the type of doping element and the microstructural structure of the ceramic, so that different heat treatment regimes should be adopted, for example, heat treatment should be carried out in stages to make the doping element enter the grain boundaries and surface more uniformly and stably, and treatments such as water washing and water quenching may be carried out between the two heat treatment stages.

[0035] The method for preparing the rare earth zirconium-based ceramic material doped on the grain boundary and surface described in the present invention adopts a wet chemical method to obtain a rare earth zirconium-based oxide powder containing doping element M, and heat-treats the rare earth zirconium-based oxide powder containing doping element M at a certain temperature, which can ensure that the doping element M is uniformly distributed on the grain boundary and surface of the rare earth zirconium-based oxide powder, and avoid the abnormality of local components from adversely affecting the overall performance of the material. Therefore, the rare earth zirconium-based ceramic material doped on the grain boundary and surface described in the present invention has higher performance than materials prepared by other methods.

[0036] In a fourth aspect of the present invention, the use of the grain boundary and surface doped rare earth zirconium-based ceramic powder material according to the first aspect of the present invention in polishing media, optical fiber connectors, mobile phone backplates, dental materials, bioceramics, thermal barrier coatings, oxygen or nitrogen oxygen sensors, and solid oxide fuel cells is provided. The grain boundary and surface doped rare earth zirconium-based ceramic powder provided in the embodiments of the present invention can be made into ceramics by molding methods such as curtain coating method and hot molding method, and can also be made into ceramic materials for application in fields such as polishing media, optical fiber connectors, mobile phone backplates, dental materials, bioceramics, thermal barrier coatings, oxygen or nitrogen oxygen sensors, and solid oxide fuel cells through structural design.

[0037] The present invention will now be further described with reference to specific examples.

[0038] Example 1 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a total cation concentration of 1.0M Y 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 10.7±0.2, the final pH value is 10.5, and the temperature is controlled to 30°C to completely precipitate the cations. The precipitate is then filtered, washed and dried, and the dried product is roasted at 600°C for 24 hours to obtain YSZ powder. YSZ is mixed with the liquid salt of lanthanum nitrate doped with La in a stoichiometric ratio, dried at 100°C for 5 hours, heat-treated at 200°C for 24 hours, and then fired at 1200°C for 2 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.05 La 0.01 Zr 0.94 O 1.97 After sintering to ceramic, the bending strength of the ceramic was 1378.28 MPa by three-point bending test.

[0039] Example 2 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added into the reactor at a constant speed, the pH value during the precipitation process is controlled to 7±0.2, the final pH value is 10.5, and the temperature is controlled to 20°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried, and the dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. YSZ is mixed with liquid salt of cerium acetate doped with a stoichiometric ratio of Ce, dried at 100°C for 5 hours, heat-treated at 300°C for 20 hours, and further fired at 700°C for 24 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.03 Ce 0.40 Zr 0.93 O 1.965 After sintering to ceramic, the bending strength of the ceramic was 1298.02 MPa by three-point bending test.

[0040] Example 3 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the mixed solution of 2.0M sodium hydroxide solution, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 5±0.2, the final pH value is 10, and the temperature is controlled to 10°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 800°C for 6 hours to obtain YSZ powder. YSZ and the liquid salt of lanthanum nitrate and lutetium nitrate doped with La and Lu in a stoichiometric ratio are mixed, dried at 100°C for 5 hours, heat-treated at 350°C for 20 hours, and further fired at 1100°C for 4 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.02 La 0.02 Lu 0.02 Zr 0.94 O 1.97 After sintering to a ceramic, the bending strength of the ceramic was 1350 MPa in a three-point bending test.

[0041] Example 4 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the mixed solution of Eu and Yb, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 4.5-11, the final pH value is 9.5, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed, and dried. The dried product is roasted at 950°C for 4 hours to obtain YSZ powder. YSZ and the liquid salts of europium nitrate and ytterbium nitrate doped with the stoichiometric ratio of Eu and Yb are mixed, dried at 100°C for 5 hours, heat-treated at 550°C for 6 hours, and further fired at 1000°C for 8 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.04 EU 0.01 Yb 0.01 Zr 0.94 O 1.97 After sintering to ceramic, the bending strength was 1310.43 MPa by three-point bending test.

[0042] Example 5 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 10.7±0.2, the final pH value is 12, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. YSZ and liquid salt of aluminum nitrate doped with stoichiometric ratio of Al are mixed, dried at 100°C for 5 hours, heat-treated at 450°C for 2 hours, and further fired at 900°C for 15 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundary and surface. 0.05 Al 0.01 Zr 0.94 O 1.97After sintering to ceramic, the bending strength was 1390.02 MPa by three-point bending test.

[0043] Example 6 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added into the reactor at a constant speed, the pH value during the precipitation process is controlled to 9±0.2, the final pH value is 10, and the temperature is controlled to 20°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried, and the dried product is roasted at 600°C for 24 hours to obtain YSZ powder. YSZ and Er stoichiometrically doped erbium nitrate liquid salt are mixed, dried at 100°C for 5 hours, heat treated at 400°C for 12 hours, and further fired at 1200°C for 2 hours to obtain rare earth zirconium ceramic powder Y doped on the grain boundary and surface. 0.09 Er 0.01 Zr 0.9 O 1.95 After sintering to ceramic, the bending strength was 570.45 MPa by three-point bending test, and the electrical conductivity at 850℃ was 32.78 mS / cm by DC four-probe method.

[0044] Example 7 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and the mixed solution and the aqueous ammonia solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 8±0.2, the final pH value is 9, and the temperature is controlled to 10°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. The YSZ and the liquid salt of scandium nitrate doped in the stoichiometric ratio of Sc are mixed, dried at 100°C for 5 hours, heat-treated at 500°C for 6 hours, and further fired at 900°C for 15 hours to obtain the rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.05 Sc 0.1Zr 0.85 O 1.925 After sintering to ceramic, its bending strength was 615.22 MPa by three-point bending test, and its electrical conductivity at 850℃ was 40.67 mS / cm by DC four-probe method.

[0045] Example 8 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and the mixed solution and the ammonia aqueous solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 8.5±0.2, the final pH value is 9, and the temperature is controlled to 20°C to completely precipitate the cations. Then, the precipitate is filtered, washed, and dried. The dried product is roasted at 650°C for 15 hours to obtain YSZ powder. YSZ and the liquid salts of ytterbium nitrate and lutetium nitrate doped with the stoichiometric ratio of Yb and Lu are mixed, dried at 100°C for 5 hours, heat-treated at 500°C for 6 hours, and further fired at 750°C for 20 hours to obtain the rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.07 Yb 0.02 Lu 0.02 Zr 0.9 O 1.945 After sintering to ceramic, the bending strength was 600 MPa by three-point bending test, and the electrical conductivity at 850℃ was 34.83 mS / cm by DC four-probe method.

[0046] Example 9 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and the ammonia aqueous solution are added into the reactor at a constant speed. The pH value during the precipitation process is controlled to 9±0.2, the final pH value is 9.5, and the temperature is controlled to 20°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. YSZ and the liquid salt of lutetium nitrate doped with Lu in a stoichiometric ratio are mixed, dried at 100°C for 5 hours, heat-treated at 550°C for 3 hours, and further fired at 1000°C for 8 hours to obtain the rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.09 Lu 0.01 Zr 0.9 O 1.95 After sintering to ceramic, the bending strength was 590.62 MPa by three-point bending test, and the electrical conductivity at 850℃ was 33.01 mS / cm by DC four-probe method.

[0047] Example 10 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and the aqueous ammonia solution are added into the reactor at a constant speed. The pH value during the precipitation process is controlled to 6±0.2, the final pH value is 9.5, and the temperature is controlled to 20°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. The YSZ and the liquid salt of scandium nitrate doped in the stoichiometric ratio of Sc are mixed, dried at 100°C for 5 hours, heat-treated at 475°C for 12 hours, fired at 900°C for 10 hours, and further fired at 1000°C for 5 hours to obtain the rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.08 Sc 0.02 Zr 0.9 O 1.95 After sintering to ceramic, the bending strength was 610.54 MPa by three-point bending test, and the electrical conductivity at 850℃ was 35.70 mS / cm by DC four-probe method.

[0048] Example 11 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and the ammonia aqueous solution are added into the reactor at a constant speed, the pH value during the precipitation process is controlled to 8±0.2, the final pH value is 9, and the temperature is controlled to 20°C to completely precipitate the cations, and then the precipitate is filtered, washed and dried, and the dried product is roasted at 700°C for 8 hours to obtain YSZ powder. YSZ is mixed with the liquid salt of scandium nitrate and gadolinium nitrate doped in the stoichiometric ratio of Sc and Gd, and is dried at 100°C for 5 hours, followed by heat treatment at 525°C for 15 hours, further heat treatment at 500°C for 3 hours, and further calcined at 1000°C for 8 hours to obtain the rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.05 Sc 0.03 Gd 0.03 Zr 0.89 O 1.945 After sintering to ceramic, the bending strength was 605.22 MPa by three-point bending test, and the electrical conductivity at 850℃ was 38.67 mS / cm by DC four-probe method.

[0049] Example 12 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned mixture, and the mixed solution and the aqueous ammonia solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 9-12, and the final pH value is 9. The temperature is controlled to 10°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. YSZ is mixed with the liquid salt of scandium nitrate and samarium nitrate doped with stoichiometric ratio of Sc and Sm, dried at 100°C for 5 hours, heat-treated at 300°C for 10 hours, further heat-treated at 575°C for 4 hours, fired at 800°C for 15 hours, and further fired at 1100°C for 3 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.06 Sc 0.03 Sm 0.01 Zr0.9 O 1.95 After sintering to ceramic, its bending strength was 625.24 MPa by three-point bending test, and its electrical conductivity at 850℃ was 36.83 mS / cm by DC four-probe method.

[0050] (Example 13) Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned mixture, and the mixed solution and sodium carbonate solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 8.5±0.2, the final pH value is 9, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 700°C for 8 hours to obtain YSZ powder. The YSZ and strontium nitrate liquid salt doped with stoichiometric ratio of Sc are mixed, dried at 100°C for 5 hours, heat-treated at 600°C for 3 hours, and further fired at 1000°C for 8 hours to obtain the rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.13 Sr 0.03 Zr 0.85 O 1.915 After sintering to ceramic, its bending strength was 389.93 MPa by three-point bending test, and its electrical conductivity at 850℃ was 81.34 mS / cm by DC four-probe method.

[0051] Example 14 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+The mixed solution is mixed with the above-mentioned, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 5.5±0.2, the final pH value is 13, and the temperature is controlled to 60°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. YSZ and Bi stoichiometrically doped liquid salt of bismuth nitrate are mixed, dried at 100°C for 5 hours, heat-treated at 575°C for 6 hours, and further fired at 1000°C for 8 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.1 Bi 0.03 Zr 0.85 O 1.925 After sintering to ceramic, the bending strength was 400 MPa by three-point bending test, and the electrical conductivity at 850℃ was 97.09 mS / cm by DC four-probe method.

[0052] Example 15 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 5-11, the final pH value is 9.5, and the temperature is controlled to 80°C to completely precipitate the cations. Then, the precipitate is filtered, washed, and dried. The dried product is roasted at 800°C for 6 hours to obtain YSZ powder. YSZ and the liquid salt of ytterbium nitrate and aluminum nitrate doped in the stoichiometric ratio of Yb and Al are mixed, dried at 100°C for 5 hours, heat-treated at 500°C for 6 hours, and further fired at 750°C for 4 hours to obtain rare earth zirconium-based ceramic powder Y doped on the grain boundary and surface. 0.12 Yb 0.03 Al 0.01 Zr 0.84 O 1.92 After sintering to ceramic, its bending strength was 420.82 MPa by three-point bending test, and its electrical conductivity at 850℃ was 85.98 mS / cm by DC four-probe method.

[0053] (Example 16) Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added into the reactor at a constant speed, the pH value during the precipitation process is controlled to 7±0.2, the final pH value is 11, and the temperature is controlled to 10°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried, and the dried product is roasted at 800°C for 6 hours to obtain YSZ powder. YSZ and the liquid salts of bismuth nitrate, ytterbium nitrate and aluminum nitrate doped in the stoichiometric ratio of Bi, Yb and Al are mixed, dried at 100°C for 5 hours, heat-treated at 500°C for 6 hours, and further fired at 1000°C for 8 hours to obtain the rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.07 Bi 0.03 Yb 0.02 Al 0.01 Zr 0.85 O 1.925 After sintering to ceramic, the bending strength was 415.05 MPa by three-point bending test, and the electrical conductivity at 850℃ was 90.00 mS / cm by DC four-probe method.

[0054] (Example 17) Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the mixed solution of YSZ and V. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed, the pH value during the precipitation process is controlled to 7±0.2, the final pH value is 9.5, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 600°C for 24 hours to obtain YSZ powder. YSZ and the liquid salt of vanadium nitrate doped with V in a stoichiometric ratio are mixed, dried at 100°C for 5 hours, heat-treated at 500°C for 3 hours, and further fired at 1100°C for 4 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.1 V 0.03 Zr 0.85 O1.925 After sintering to ceramic, the bending strength was 400.79 MPa by three-point bending test, and the electrical conductivity at 850℃ was 73.65 mS / cm by DC four-probe method.

[0055] (Example 18) Stoichiometric ratios of scandium nitrate and zirconium oxynitrate were dissolved in water to obtain a concentration of 1.0M Sc. 3+ and Zr 4+ The mixed solution is mixed with the mixed solution of ScSZ and Yb. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed, the pH value during the precipitation process is controlled to 5.5±0.2, the final pH value is 8, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain ScSZ powder. ScSZ and the liquid salt of ytterbium nitrate doped with Yb in a stoichiometric ratio are mixed, dried at 100°C for 5 hours, heat-treated at 425°C for 6 hours, and further fired at 900°C for 15 hours to obtain the rare earth zirconium ceramic powder ScSZ doped on the grain boundary and surface. 0.14 Yb 0.04 Zr 0.82 O 1.91 After sintering to a ceramic, the electrical conductivity at 850℃ was 190.88mS / cm by DC four-probe method.

[0056] (Example 19) Stoichiometric ratios of scandium nitrate and zirconium oxynitrate were dissolved in water to obtain a concentration of 1.0M Sc. 3+ and Zr 4+The mixed solution is mixed with the mixed solution of ScSZ and Ce. Under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added into the reactor at a constant speed. The pH value during the precipitation process is controlled to 5.5±0.2, the final pH value is 9, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain ScSZ powder. ScSZ and Ce stoichiometrically doped cerium nitrate liquid salt are mixed, dried at 100°C for 5 hours, heat-treated at 500°C for 6 hours, and further fired at 850°C for 15 hours to obtain the rare earth zirconium ceramic powder ScSZ doped on the grain boundary and surface. 0.14 Ce 0.03 Zr 0.82 O 1.91 After sintering to a ceramic, the electrical conductivity at 850℃ was 185.72mS / cm by DC four-probe method.

[0057] (Example 20) Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 10-14, and the final pH value is 9.5. The temperature is controlled to 60°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 650°C for 15 hours to obtain YSZ powder. YSZ and Ni-doped nickel citrate liquid salt are mixed, dried at 100°C for 5 hours, heat-treated at 400°C for 12 hours, and then fired at 900°C for 15 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.05 Ni 0.03 Zr 0.92 O 1.96 After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1200℃, and the fracture toughness was 2.94MPa m 1 / 2After spraying, a thermal shock cycling test was conducted, with the thermal shock cycling cycle being 248 times (the thermal shock cycling test was conducted by heating and holding for 50 minutes in a box furnace at 1150°C, then removing and cooling in air at room temperature for 10 minutes; this was repeated multiple times, and the coating was judged to have failed until the area where it had peeled off from the substrate reached 10%. The thermal shock cycling test described below is the same as this example).

[0058] Example 21 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the mixed solution of 1.0M sodium hydroxide solution, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 10±0.2, the final pH value is 10.5, and the temperature is controlled to 20°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. YSZ and the liquid salt of zinc acetate doped with stoichiometric ratio of Zn are mixed, dried at 100°C for 5 hours, heat-treated at 400°C for 12 hours, and further fired at 900°C for 15 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundary and surface. 0.05 Zinc 0.03 Zr 0.92 O 1.96 After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1200℃, and the fracture toughness was 2.88MPa m 1 / 2 After thermal spraying, a thermal shock cycling test was carried out, and the number of thermal shock cycling cycles was 256.

[0059] Example 22 Stoichiometric ratios of yttrium chloride and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+The mixed solution is mixed with the mixed solution of YSZ and Mg. Under stirring conditions, the mixed solution and magnesium bicarbonate solution are added to the reactor at a constant speed, the pH value during the precipitation process is controlled to 4.7±0.2, the final pH value is 8.5, and the temperature is controlled to 20°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder. YSZ and magnesium nitrate liquid salt doped with stoichiometric ratio of Mg are mixed, dried at 100°C for 5 hours, heat-treated at 300°C for 20 hours, and further fired at 800°C for 17 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundary and surface. 0.05 Mg 0.03 Zr 0.92 O 1.825 After sintering to ceramic, phase analysis showed that it could maintain the stability of the phase structure below 1200℃, and the fracture toughness was 3.03MPa m 1 / 2 After thermal spraying, a thermal shock cycle test was carried out, and the thermal shock cycle was repeated 320 times.

[0060] (Example 23) Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed, the pH value during the precipitation process is controlled to 7±0.2, the final pH value is 10, and the temperature is controlled to 10°C to completely precipitate the cations. Then, the precipitate is filtered, washed, and dried, and the dried product is roasted at 800°C for 6 hours to obtain YSZ powder. YSZ is mixed with aluminum nitrate and samarium nitrate liquid salts doped with a stoichiometric ratio of Al and Sm, dried at 100°C for 5 hours, heat-treated at 400°C for 12 hours, and further fired at 1050°C for 2 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.05 Sm 0.02 Al 0.01 Zr 0.92 O 1.96After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1200℃, and the fracture toughness was 2.12MPa m 1 / 2 After thermal spraying, a thermal shock cycling test was carried out, and the number of thermal shock cycling cycles was 417.

[0061] Example 24 Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed, the pH value during the precipitation process is controlled to 6±0.2, the final pH value is 11, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried, and the dried product is roasted at 950°C for 4 hours to obtain YSZ powder. YSZ and praseodymium nitrate liquid salt doped with stoichiometric ratio of Pr are mixed, dried at 100°C for 5 hours, heat-treated at 550°C for 12 hours, and further fired at 1150°C for 2 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundary and surface. 0.04 Pr 0.04 Zr 0.92 O 1.973 After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1200℃, and the fracture toughness was 2.50MPa m 1 / 2 After thermal spraying, a thermal shock cycling test was carried out, and the thermal shock cycling number was 301 times.

[0062] (Example 25) Stoichiometric ratios of yttrium nitrate and zirconium oxynitrate are dissolved in water to obtain a concentration of 1.0M Y. 3+ and Zr 4+The mixed solution is mixed with the mixed solution of the above, and under stirring conditions, the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed, the pH value during the precipitation process is controlled to 8.5±0.2, the final pH value is 9.5, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried, and the dried product is roasted at 600°C for 24 hours to obtain YSZ powder. YSZ is mixed with liquid salts of neodymium nitrate and gadolinium nitrate doped in a stoichiometric ratio of Nd and Gd, dried at 100°C for 5 hours, heat-treated at 400°C for 12 hours, and further fired at 1200°C for 2 hours to obtain rare earth zirconium-based ceramic powder Y doped with grain boundaries and surfaces. 0.06 Nd 0.02 Gd 0.02 Zr 0.9 O 1.95 After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1200℃, and the fracture toughness was 2.86MPa m 1 / 2 After thermal spraying, a thermal shock cycling test was carried out, and the thermal shock cycling was repeated 450 times.

[0063] (Example 26) Stoichiometric ratios of lanthanum nitrate and zirconium oxynitrate were dissolved in water to obtain a concentration of 0.5M La 3+ and Zr 4+ The mixed solution is mixed with the mixed solution of LaZO and Sc, and the mixed solution and the ammonia aqueous solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 6±0.2, the final pH value is 9.5, and the temperature is controlled to 50°C to completely precipitate the cations. Then, the precipitate is filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain LaZO powder. The liquid salt of scandium nitrate doped with LaZO and Sc in a stoichiometric ratio is mixed, dried at 100°C for 5 hours, heat-treated at 400°C for 12 hours, and fired at 950°C for 10 hours to obtain the rare earth zirconium ceramic powder LaZO doped on the grain boundary and surface. 0.34 Sc 0.1 Zr 0.55After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1500℃, and the fracture toughness was 1.39MPa m 1 / 2 After thermal spraying, a thermal shock cycle test was carried out, and the thermal shock cycle was repeated 39 times.

[0064] Example 27 Stoichiometric ratios of gadolinium nitrate and zirconium oxynitrate were dissolved in water to obtain a concentration of 1.5M Gd 3+ and Zr 4+ The mixed solution is mixed with the mixture of GdZO and Yb, and the mixed solution and the ammonia aqueous solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 6±0.2, the final pH value is 9.5, and the temperature is controlled to 50°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 900°C for 5 hours to obtain GdZO powder. GdZO and the liquid salt of ytterbium nitrate doped with Yb in a stoichiometric ratio are mixed, dried at 100°C for 5 hours, heat-treated at 400°C for 5 hours, and fired at 950°C for 10 hours to obtain the rare earth zirconium ceramic powder Gd 0.28 Yb 0.15 Zr 0.57 O 1.71 After sintering to ceramic, phase analysis showed that it could maintain the stability of the phase structure below 1500℃, and the fracture toughness was 2.56MPa m 1 / 2 After thermal spraying, a thermal shock cycle test was carried out, and the thermal shock cycle count was 109.

[0065] (Example 28) Stoichiometric ratios of gadolinium nitrate and zirconium oxynitrate were dissolved in water to obtain a concentration of 2.0M Gd 3+ and Zr 4+The mixed solution is mixed with the above mixture, and the mixed solution and the aqueous ammonia solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 6±0.2, the final pH value is 9.5, and the temperature is controlled to 50°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 900°C for 5 hours to obtain GdZO powder. GdZO and the liquid salt of ytterbium nitrate doped with Yb in a stoichiometric ratio are mixed, dried at 100°C for 5 hours, heat-treated at 400°C for 12 hours, and fired at 950°C for 10 hours to obtain the rare earth zirconium ceramic powder Gd 0.46 Yb 0.05 Zr 0.5 O 1.725 After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1500℃, and the fracture toughness was 1.59MPa m 1 / 2 After thermal spraying, a thermal shock cycling test was carried out, and the number of thermal shock cycling cycles was 41.

[0066] (Example 29) Stoichiometric ratios of gadolinium nitrate and zirconium oxynitrate were dissolved in water to obtain a concentration of 2.0M Gd 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned mixture, and the mixed solution and the ammonia aqueous solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 5-10, the final pH value is 9.5, and the temperature is controlled to 30°C to completely precipitate the cations. Then, the precipitate is filtered, washed, and dried. The dried product is roasted at 900°C for 24 hours to obtain GdZO powder. GdZO is mixed with the liquid salt of ytterbium nitrate and yttrium nitrate doped with the stoichiometric ratio of Yb and Y, dried at 100°C for 5 hours, heat-treated at 400°C for 12 hours, and fired at 1200°C for 2 hours to obtain the rare earth zirconium ceramic powder Gd 0.4 Yb 0.05 Y 0.05 Zr 0.5 O 1.75After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1500℃, and the fracture toughness was 1.72MPa m 1 / 2 After thermal spraying, a thermal shock cycle test was carried out, and the thermal shock cycle was repeated 49 times.

[0067] Comparative Example 1 Stoichiometric ratios of yttrium chloride, lanthanum nitrate, and zirconium oxychloride were dissolved in water to obtain a concentration of 1.0M Y. 3+ , La 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 10.7±0.2, and the final pH value is 10.5. The temperature is controlled at 30°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 600°C for 24 hours to obtain YSZ powder, which is then fired at 1200°C for 2 hours to obtain rare earth zirconium ceramic powder Y. 0.05 La 0.01 Zr 0.94 O 1.97 After sintering to ceramic, the bending strength of the ceramic was 1035.71 MPa by three-point bending test.

[0068] Comparative Example 2 Stoichiometric ratios of yttrium chloride, scandium nitrate, and zirconium oxychloride were dissolved in water to obtain a solution with a concentration of 1.0M Y. 3+ , Sc 3+ and Zr 4+ The mixed solution is mixed with the above, and the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 5±0.2, the final pH value is 10, and the temperature is controlled to 10°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 800°C for 6 hours to obtain YSZ powder, which is then fired at 1100°C for 4 hours to obtain rare earth zirconium ceramic powder Y. 0.05 Sc 0.05 Zr 0.9 O 1.95After sintering to ceramic, the bending strength was 520.23 MPa by three-point bending test, and the electrical conductivity at 850℃ was 30.45 mS / cm by DC four-probe method.

[0069] Comparative Example 3 Stoichiometric ratios of yttrium chloride, bismuth nitrate, and zirconium oxychloride were dissolved in water to obtain a concentration of 1.0M Y. 3+ , Bi 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 5.5±0.2, and the final pH value is 13. The temperature is controlled to 60°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder, which is then fired at 1000°C for 8 hours to obtain rare earth zirconium ceramic powder Y. 0.1 Bi 0.03 Zr 0.85 O 1.925 After sintering to ceramic, its bending strength was 353.49 MPa by three-point bending test, and its electrical conductivity at 850℃ was 71.20 mS / cm by DC four-probe method.

[0070] Comparative Example 4 Stoichiometric ratios of scandium nitrate, ytterbium nitrate, and zirconium oxynitrate were dissolved in water to obtain a concentration of 1.10M Sc. 3+ , Yb 3+ and Zr 4+ The mixed solution is mixed with the above mixture, and the mixed solution and 3.0M ammonia aqueous solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 5.5±0.2, the final pH value is 9, and the temperature is controlled to 30°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain ScSZ powder, which is then fired at 900°C for 15 hours to obtain rare earth zirconium ceramic powder ScSZ. 0.14 Yb 0.04 Zr 0.82 O 1.91After sintering to a ceramic, the electrical conductivity at 850℃ was 165.23mS / cm by DC four-probe method.

[0071] Comparative Example 5 Stoichiometric ratios of yttrium chloride, magnesium nitrate, and zirconium oxychloride are dissolved in water to obtain a concentration of 1.0M Y. 3+ , Mg 2+ and Zr 4+ The mixed solution is mixed with the above-mentioned, and the mixed solution and magnesium bicarbonate solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 4.7±0.2, and the final pH value is 8.5. The temperature is controlled at 20°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain YSZ powder, which is then fired at 800°C for 17 hours to obtain rare earth zirconium ceramic powder Y. 0.05 Mg 0.03 Zr 0.92 O 1.96 After sintering to ceramic, phase analysis showed that it could maintain the phase structure stability below 1200℃, and the fracture toughness was 2.76MPa m 1 / 2 After thermal spraying, a thermal shock cycle test was carried out and the number of thermal shock cycles was determined to be 250.

[0072] Comparative Example 6 Stoichiometric ratios of lanthanum nitrate, scandium nitrate, and zirconium oxynitrate were dissolved in water to obtain a concentration of 0.5M La 3+ , Sc 3+ and Zr 4+ The mixed solution is mixed with the mixture of the above, and the mixed solution and the ammonia aqueous solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 6±0.2, and the final pH value is 9.5. The temperature is controlled to 50°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 1000°C for 2 hours to obtain LaZO powder, which is then fired at 950°C for 10 hours to obtain rare earth zirconium ceramic powder LaZO. 0.4 Sc 0.1 Zr 0.5 O 1.75After sintering to ceramic, phase analysis showed that it could maintain the stability of the phase structure below 1500℃, and the fracture toughness was 1.12MPa m 1 / 2 After the thermal spraying, a thermal shock cycling test was carried out, and the thermal shock cycling was repeated 30 times.

[0073] Comparative Example 7 Dissolve yttrium chloride and zirconium oxychloride in water in a stoichiometric ratio to make a total concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 10.7±0.2, and the final pH value is 10.5. The temperature is controlled at 30°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 600°C for 24 hours to obtain YSZ powder, which is ball-milled and mixed with ethylene glycol in a stoichiometric ratio of YSZ and lanthanum oxide, and then fired at 1200°C for 2 hours to obtain rare earth zirconium ceramic powder Y. 0.05 La 0.01 Zr 0.94 O 1.97 After sintering to ceramic, the bending strength was 987.21 MPa by three-point bending test.

[0074] Comparative Example 8 Dissolve yttrium chloride and zirconium oxychloride in water in a stoichiometric ratio to make a total concentration of 1.0M Y. 3+ and Zr 4+ The mixed solution is mixed with the above-mentioned, and the mixed solution and 2.0M sodium hydroxide solution are added to the reactor at a constant speed under stirring conditions. The pH value during the precipitation process is controlled to 10.7±0.2, and the final pH value is 10.5. The temperature is controlled at 30°C to completely precipitate the cations. The precipitate is then filtered, washed and dried. The dried product is roasted at 600°C for 24 hours to obtain YSZ powder. YSZ is mixed with the liquid salt of lanthanum nitrate doped with La in a stoichiometric ratio, and further fired at 1200°C for 2 hours to obtain rare earth zirconium-based ceramic powder Y doped with YSZ and La. 0.05 La 0.01 Zr0.94 O 1.97 After sintering to ceramic, the bending strength was 1107.80 MPa by three-point bending test.

[0075] As is apparent from the above examples, the rare earth zirconium-based ceramic powder manufactured according to the embodiments of the present invention has significantly improved bending strength, electrical conductivity, fracture toughness and thermal shock cycle number compared to the comparative examples, and can obtain significantly beneficial technical effects.

[0076] As described above, the present invention provides a rare earth zirconium-based ceramic material doped with grain boundaries and surfaces, and its manufacturing method and use, and the grain boundaries and surfaces of the rare earth zirconium-based ceramic material are doped with M oxide by the grain boundary doping method, and the sintering activity of the rare earth zirconium-based ceramic material can be changed according to different kinds and contents of doping elements, thereby adjusting the crystal grain size, grain boundary number and properties of the rare earth zirconium-based ceramic material, and finally optimizing the electrical, mechanical, thermal and other properties of the material. The grain boundary and surface doping method provided in the technical solution of the present invention is versatile and can realize the efficient and low-cost adjustment of the grain boundary properties of the rare earth zirconium-based ceramic material, thereby improving the performance of the rare earth zirconium-based ceramic material and meeting the demands for doping elements of different rare earth zirconium-based ceramic materials.

[0077] It should be understood that the above specific embodiments of the present invention are merely used for illustrative purposes to explain or explain the principles of the present invention, and are not intended to limit the present invention. Therefore, any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and scope of the present invention should be included within the protection scope of the present invention. Furthermore, the claims of the present invention are intended to include all changes and modifications within the scope and limits of the claims, or equivalent forms of such scope and limits.

Claims

1. In the rare earth zirconium-based ceramic material doped on the grain boundary and the surface, the chemical formula of the rare earth zirconium-based ceramic material is RE x Zr 1-x-y M y O 2-z where: RE is a rare earth element, M is a cationic doping element, A grain boundary and surface doped rare earth zirconium based ceramic material, characterized in that 0.03≦x≦0.5, 0<y≦0.15, and 0.01≦z<0.

3.

2. 2. The doped rare earth zirconium ceramic material according to claim 1, characterized in that the grain boundaries and surface of said rare earth zirconium ceramic material contain an oxide of the doping element M.

3. 2. The grain boundary and surface doped rare earth zirconium based ceramic material according to claim 1, wherein said RE is one or a combination of one or more of Sc, Y, La, Gd and Ce.

4. 2. The grain boundary and surface doped rare earth zirconium based ceramic material of claim 1, wherein M comprises one or a combination of one or more of cationic transition metal elements, alkaline earth metal elements, Al, Ga, In, Ge, Sn, Sb, Bi, Si, and rare earth elements.

5. 5. The grain boundary and surface doped rare earth zirconium based ceramic material according to claim 4, characterized in that M comprises one or a combination of one or more of Mg, Ca, Sr, Al, Ga, V, Fe, Mn, Ni, Zn, Nb, In, Bi and rare earth elements, preferably one or a combination of one or more of Mg, Sr, Al, V, Ni, Bi, La, Ce, Pr, Nd, Sm, Eu, Gd, Er, Yb, Lu, Y and Sc, more preferably one or a combination of one or more of Mg, Al, Ni, Bi, La, Ce, Gd, Yb and Lu.

6. The grain boundary and surface doped rare earth zirconium based ceramic material according to claim 5, characterized in that the molar content of M in the rare earth zirconium based ceramic material is less than 15%, preferably less than 10%.

7. The grain boundary and surface doped rare earth zirconium based ceramic material according to claim 1, characterized in that the rare earth zirconium based ceramic material is one or more of the following: cubic fluorite structure, tetragonal phase, monoclinic phase and rhombohedral phase, preferably one or two of the following: cubic fluorite structure and tetragonal phase.

8. Step S1: mixing aqueous solutions of RE and Zr compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; filtering, washing, drying and roasting the obtained precipitate to obtain a rare earth zirconium oxide powder; and step S2, in which the rare earth zirconium-based oxide powder material obtained in step S1 is mixed with a liquid salt of a doping element M, and after drying, is subjected to one or two heat treatments, and further subjected to one or two firings to obtain a rare earth zirconium-based ceramic material doped on the grain boundaries and the surface thereof.

9. Step S1: mixing aqueous solutions of RE, Zr and a part of M compounds in a stoichiometric ratio required for the product to obtain a mixed solution; adding the mixed solution and a basic substance to a reactor to carry out a precipitation reaction; filtering, washing, drying and roasting the obtained precipitate to obtain a rare earth zirconium-based oxide powder containing M element; and step S2 of mixing the rare earth zirconium-based oxide powder containing the M element obtained in step S1 with the liquid salt of the remaining doping element M, drying the mixture, subjecting it to one or two heat treatments, and further subjecting it to one or two firings to obtain a rare earth zirconium-based ceramic material doped at the grain boundaries and on the surface thereof.

10. 10. The method according to claim 8 or 9, wherein the aqueous solution containing Zr in step S1 comprises one or a combination of one or more aqueous solutions of zirconium oxychloride, zirconium oxynitrate, zirconium oxysulfate, zirconium acetate, and zirconium citrate.

11. 10. The method according to claim 8 or 9, characterized in that the aqueous solution containing RE in step S1 comprises one or a combination of one or more aqueous solutions of rare earth chlorides, nitrates, sulfates, acetates and citrates.

12. 10. The method according to claim 8 or 9, characterized in that the liquid salts of doping elements M comprise one or a combination of one or more of the following molten salts or aqueous solutions of chlorides, nitrates, sulfates, acetates, citrates and amino acid salts.

13. 10. The method according to claim 8 or 9, characterized in that the basic substance comprises at least one of magnesium hydrogen carbonate, urea and hydroxide, carbonate or hydrogen carbonate of at least one element of ammonium, sodium and potassium, preferably at least one of sodium hydroxide, urea, aqueous ammonia and ammonium hydrogen carbonate.

14. The method according to claim 8 or 9, characterized in that the pH value during the precipitation in step S1 is controlled to be 4.5-14, preferably 5-11, the pH value at the end of the precipitation is controlled to be 8-13, preferably 9-11, and the temperature during the precipitation is 0-120°C, preferably 10-80°C.

15. The method according to claim 8 or 9, characterized in that the roasting temperature in step S1 is 600-1100 ° C, preferably 650-950 ° C, and the roasting time is 1-24 h, preferably 3-15 h.

16. The method according to claim 8 or 9, characterized in that the heat treatment temperature described in step S2 is 200 to 750 ° C, preferably 400 to 600 ° C, more preferably 400 to 550 ° C, and the heat treatment time is 1 to 24 h, preferably 1 to 12 h.

17. The method according to claim 8 or 9, characterized in that the firing temperature described in step S2 is 700 to 1200 ° C, preferably 800 to 1100 ° C, more preferably 900 to 1100 ° C, and the time is 1 to 24 h, preferably 3 to 15 h.

18. Applications of the grain boundary and surface doped rare earth zirconium based ceramic powder material according to any one of claims 1 to 7 in the fields of polishing media, fiber optic connectors, mobile phone backplates, dental materials, bioceramics, thermal barrier coatings, oxygen or nitrogen oxygen sensors, and solid oxide fuel cells.

Citation Information

Patent Citations

  • Cerium-zirconium-based composite oxide with core-shell structure, and preparation method thereof

    CN111939894A

  • Rare earth manganese / cerium zirconium composite compound with core-shell structure, preparation method and catalyst

    CN112439407A

  • Production of zirconia sintered product

    JP1993170532A

  • Zirconia-based composite ceramic sintered compact and its production

    JP1998101418A

  • Zirconia sintered compact and its producing method

    JP2004262694A